Construcción de un concepto de prevención del uso indebido de drogas (1996)
ABSTRACT: The objetive of prevention of psychoactive substance misuse or inappropriate use of drugs (IUD) is the intervention on risk factor the may increase the use of drugs in populations and, consequently, the deterioration of the quiality of life of the communities.To achieve this objectivr it is necessary to build up a concep of prevention associated to UID, keeping in mind the munltiple paradigms th attempt to explain this topic. The methods used to understand the UID and its prevention, in addition to the ethnic and cultural realities , contribute to understand the lack of knowledge about the causes of the problem and most expeditious ways to make prevention efforts. Despite this current lack of knowledge, prevention is becoming a system in which the components are identified, as well, the multiple strategies with which one of them participate. This allows to adapt them to the requirements of the environment where "participation" becomes an essential factor to obtain the expected results, according to previously conducted assessments of the situation. These components are: education, research, normalization, intervention, and communication. Due to the multiple causes of UID, there have been developed multiple strategies and levels of intervention in what is called "comprehensive prevention." The purpose of this paper is to share some of the conclusions regarding the concept of prevention of UID reached as a result of the tem work at the Corporacion SURGIR, whose mission is to prevent the use of drugs in the community.